Effects of 4 Weeks of High-Definition Transcranial Direct Stimulation and Foot Core Exercise on Foot Sensorimotor Function and Postural Control - Xiao, Songlin; Wang, Baofeng; Zhang, Xini; Zhou, Junhong; Fu, Weijie (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: This study aims to examine the effects of 4 weeks of high-definition transcranial direct current stimulation (HD-tDCS) and foot core exercise (FCE) on foot sensorimotor function (i.e., toe flexor strength and passive ankle kinesthesia) and postural control. Methods: Thirty-six participants were randomly assigned into three groups as follows: HD-tDCS, FCE, and control group. A total of 12 training sessions were performed over 4 weeks (i.e., three sessions per week) in the laboratory. The HD-tDCS group received 20-minute HD-tDCS with a current density of 2 mA, and the FCE group completed short foot exercise, towel curls, toe spread and squeeze, and balance board training. Participants in the control group just maintained the activities as what they usually did and did not receive any interventions. Foot muscle strength, passive ankle kinesthesia, and postural control were assessed at baseline and post-intervention. Results: HD-tDCS induced a greater decrease in the percent changes in the passive kinesthesia thresholds of ankle inversion (p < 0.001) and eversion (p = 0.013) than the control group. Compared with the control group, a significant increase in the percent change in metatarsophalangeal joint flexor strength was found in the HD-tDCS group (p = 0.008) and FCE group (p = 0.027), and a significant increase in percent change in toe flexor strength was observed in the FCE group (p = 0.015). Besides, FCE induced a greater reduction in the percent changes in the medial–lateral average center of gravity sway velocity in one-leg standing with eyes open (p = 0.033) and anteroposterior average center of gravity sway velocity in one-leg standing with eyes closed (p < 0.001) than control. Conclusion: This study demonstrated that four weeks of HD-tDCS and FCE induced distinct benefits on foot sensorimotor function and the standing postural control performance in healthy young adults. HD-tDCS could improve metatarsophalangeal joint flexor strength and the passive kinesthesia thresholds of ankle inversion and eversion. Meanwhile, FCE could also enhance foot muscle strength and enhance postural control performance in one-leg standing.